Streaming Science #5: Using Virtual Reality Tours for Engagement With Your Target Audience - Jamie Loizzo; Gabriel Spandau; Caroline Barnett; Alice Akers; Alexis Bolger; Courtney Meyers (EDIS)
This is the fifth of seven publications in the Streaming Science EDIS series about using mobile instructional and communication technologies (ICTs) for outreach and engagement with your target audiences. This publication is intended as a guide for communication and education professionals to use various virtual reality (VR) hardware and software to create immersive online content about agricultural and natural resources spaces and places to communicate, teach, and engage with scientific content.